Penilaian dan Evaluasi Media Stop Motion Berbasis Pendekatan Inquiry Materi Sumber Daya Alam - Miftahurrahmi, Miftahurrahmi; Herlinda, Herlinda; Vebrianto, Rian; Radeswandri, Radeswandri (Mitra PGMI: Jurnal Kependidikan MI, 2023)
Learning media is a learning resource that can facilitate the learning process. The era of the 21st century as it is today increasingly developing, making the media increasingly innovate in accordance with what is currently industry 4.0. For this reason, the researchers assessed and evaluated the media that had been developed in the form of stop motion media based on an inquiry approach with Lee & Owens instructional materials on natural resources. The methodology used in this research is Research and Development research. This study involved 8 experts, 5 teachers and 3 lecturers, to validate the media using media validation instruments (media, language, and technology). Meanwhile, to assess the practicality of using media practicality instruments to see the effectiveness of the media by involving 30 students and 15 teachers in accordance with the scientific data were taken using the Google form and direct meetings with respondents. Data were analyzed using SPSS descriptively to reproduce the results of the media assessment. The results of this study are for the validation instrument it is known that the results of technologist (3.59%), media (3.75%) and language (3.62%) while for practical instruments it is known that teachers (3.70%) and students (3 .73%) in this case the media used is valid and has effectiveness and efficiency in an effective teaching and learning process.